Відповідь:
[tex]\frac{1}{2} *8-\frac{1}{2} *3\frac{1}{2} x=-1\frac{1}{4}x-4\frac{1}{2}[/tex]
[tex]4-1\frac{3}{4} x=-1\frac{1}{4}x-4\frac{1}{2}[/tex]
[tex]-1\frac{3}{4} x+1\frac{1}{4}x=-4\frac{1}{2} -4[/tex]
[tex]-\frac{1}{2} x=-8\frac{1}{2}[/tex]
[tex]x=-8\frac{1}{2} :( -\frac{1}{2})[/tex]
[tex]x=\frac{17*2}{2*1}[/tex]
x=17
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Відповідь:
[tex]\frac{1}{2} *8-\frac{1}{2} *3\frac{1}{2} x=-1\frac{1}{4}x-4\frac{1}{2}[/tex]
[tex]4-1\frac{3}{4} x=-1\frac{1}{4}x-4\frac{1}{2}[/tex]
[tex]-1\frac{3}{4} x+1\frac{1}{4}x=-4\frac{1}{2} -4[/tex]
[tex]-\frac{1}{2} x=-8\frac{1}{2}[/tex]
[tex]x=-8\frac{1}{2} :( -\frac{1}{2})[/tex]
[tex]x=\frac{17*2}{2*1}[/tex]
x=17